2009
DOI: 10.1002/jmv.21467
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony stimulating factor in HCV genotype‐1 patients who develop Peg‐IFN‐α2b related severe neutropenia: A preliminary report on treatment, safety and efficacy

Abstract: Dose reductions of Peg-IFNa because of severe neutropenia may affect the virologic response in patients with hepatitis C infection (HCV). Granulocyte colony-stimulating factor (G-CSF) has been used occasionally but studies addressing its safety and efficacy in the current treatment of HCV infection are missing. The database of 232 naïve patients with HCV genotype-1 who received PEG-IFNalpha2b 1.5 mcg/kg/week plus Ribavirin 800-1,400 mg/day and completed the treatment was examined. Nineteen patients who exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Through sponsor contact, we received data from a clinical trial evaluating the efficacy of combination therapy with Peg‐IFN plus ribavirin [9]. Overall, 19 unique studies addressed effectiveness [9,27,28,31,32,35,36,38–41] and safety [24–26,29,30,33,34,37]. There was one RCT [32], three retrospective cohort studies [27–29] and 15 case series [9,24–26,30,31,33–41].…”
Section: Systematic Review Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through sponsor contact, we received data from a clinical trial evaluating the efficacy of combination therapy with Peg‐IFN plus ribavirin [9]. Overall, 19 unique studies addressed effectiveness [9,27,28,31,32,35,36,38–41] and safety [24–26,29,30,33,34,37]. There was one RCT [32], three retrospective cohort studies [27–29] and 15 case series [9,24–26,30,31,33–41].…”
Section: Systematic Review Resultsmentioning
confidence: 99%
“…Hepatitis C virus (HCV) therapy varied across studies (Table 1). The definition of neutropenia ranged from neutrophil count <0.75 × 10 9 /L [9,24–26,30–32,34,36,37] to <1.0 × 10 9 /L [27–29,33,41]. In two studies, neutropenia was defined as a white blood cell count <3000/μL [38] or <2000/nL [40].…”
Section: Systematic Review Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Some preliminary reports suggest that more patients can experience a sustained virologic response when full-dose interferon therapy is continued with G-CSF support; however, rigorous randomized controlled studies are needed before routine use of G-CSF can be recommended in this setting. 46,47 Neutropenia caused by immunosuppressive medications, cytomegalovirus infection, antiviral therapy, or a combination thereof may also occur in patients who receive solid organ transplants. Neutropenia has been documented in 28% of renal transplant recipients in the first year posttransplant.…”
Section: Prevention Of Infection In Patients With Nonmalignant Neutromentioning
confidence: 98%
“…In a recent retrospective, cross-sectional study, Koskinas et al [53] found that HCV patients who were given G-CSF while undergoing combination therapy had higher rates of SVR (32% vs 21%), but this result was not statistically significant. Interestingly, the authors of this study found that members of the G-CSF group had higher rates of treatment adherence (95% vs 73.1%, P  < 0.05).…”
Section: Management Of Adverse Reactionsmentioning
confidence: 99%